INDUKSI DAN PERTUMBUHAN KALUS BATANG MELATI (JASMINUM SAMBAC) PADA MEDIA MS DENGAN PENAMBAHAN GIBERELIN - NURMALITA SARI YULIA, EKA Nurmalita-Sari (LenteraBio: Berkala Ilmiah Biologi, 2012)
Plants jasmine (Jasminum sambac) is a plant that has many benefits in agriculture and health, because they contain tannin, volatile oil, hesperidin, daucosterol and essential oil. Propagation techniques traditionally jasmine by stem cuttings are many obstacles encountered among others, the quality of seedlings produced less good, percentage of rooted cuttings and sprout is not too much. This problem can be overcome by tissue culture. The purpose of this study was to determine  the effect of various gibberellins concentration on callus induction and growth (long induction, callus mass and texture of the callus) internodus jasmine (Jasminum sambac). This research method using a completely randomized design (CRD) with one parameter namely the addition of an organizing growing gibberellins with 5 different concentration are, 6 ppm, 5,5 ppm, 5 ppm, 4,5 ppm, and 4 ppm. Each treatment was repeated 5 times. Parameters observed was old callus induction, callus mass, and texture of the callus. The data obtained were analyzed using qualitative descriptive analysis and test one way anova and if there is a difference followed by Duncan test. The results showed that treatment C at a concentration of 5 ppm can result in the fastest time of induction, the greatest mass and produced callus friable  texture.